Pathogenic Vibrios Associated with Seafoods in and Around Kakinada, India • tn - M.M., Prasad; C.C., Panduranga Rao (Fishery Technology, 2025)
Investigations on the prevalence of pathogenic vibrios were attempted in 129 samples of fresh, frozen and iced prawn and fish. Thirty percent of the prawn Penaeus indicus carried vibrio species comprising Vibrio parahaemolyticus, V. vulnificus, V. metchnikovii, V. cholerae Non 01, V. anguillarum and Group F vibrios. Maximum number of isolates were found to be V. cholerae Non 01. Incidence of pathogenic vibrios were lower in fish compared to prawn.